(untitled) (Journal of Medical Sciences, 2024)
Background: Bad breath, or halitosis, is an uncomfortable or repulsive odour coming from the mouth. It is complex and can have both oral and systemic causes, as well as be linked to certain illnesses. The purpose of the study was to evaluate bad breath as a result of health issues as reported by parents whose children are receiving care at the Children’s Regional Hospital in Benghazi Subjects and methods: Ethical approval permission (3.1) was obtained and informed parent and child consent was sought. One hundred and sixty parents (160) accompanying their children, including inpatients and outpatients attended a children’s hospital in Benghazi, Libya. They were personally interviewed with their children and written questionnaires were previously prepared. Every parent was questioned regarding their thoughts and experiences regarding their child’s bad breath and related health issues. They were subsequently entered into the survey form. The accompanied children ranged in age from 2 to 12 years old and had various health issues. Findings: The mean age was 6.8, and the male-to-female ratio was 52.5 to 47.5%. Parents’ or other people’s perception of children’s bad breath as a result of breathing through their mouths due to nasal issues was 96 (60.0%), which was highly significant at p≤0.05. 48.8% overall had respiratory problems, 36% had tonsillitis, 49.3% had sinusitis, and 12% (n=19) had GIT issues. . The intensity of bad breath varied from mild to very severe smelly. Conclusion: Bad breath released from systemically infected children is perceived by the parents or others showed another major cause rather than an oral cause for bad smell.